Numerical Approach to the Assessment of Air Pollution by Solid-Fuel Combustion Products; Chemical and Petroleum Engineering; Vol. 53, iss. 1-2 - Gvozdyakov D. V. Dmitry Vasilievich (2017, 2017)
Title screen